PERANCANGAN IKLAN LAYANAN MASYARAKAT BAHAYA CYBERCRIME DALAM BENTUK MOTION GRAPHIC - Ekoprabowo, Raihan Widi (Institut Seni Indonesia Yogyakarta, 2020)
. Motion Graphic is a trendy audio visual media to inform nowadays.With the massive technology growth people are addicted to internet.Everybody is able to use internet start with kids and until elderly are able to use internet.Because of that some of villain take the advantages from it,they use internet for robbing people without making any physical contact to the victim.So the design of this public advertise is to give warn message to all people that using internet to be warn from cybercrime.